2009
DOI: 10.4315/0362-028x-72.1.37
|View full text |Cite|
|
Sign up to set email alerts
|

Enterobacter sakazakii in Dried Infant Formulas and Milk Kitchens of Maternity Wards in São Paulo, Brazil

Abstract: This study was the first conducted in Brazil to evaluate the presence of Enterobacter sakazakii in milk-based powdered infant formula manufactured for infants 0 to 6 months of age and to examine the conditions of formula preparation and service in three hospitals in São Paulo State, Brazil. Samples of dried and rehydrated infant formula, environments of milk kitchens, water, bottles and nipples, utensils, and hands of personnel were analyzed, and E. sakazakii and Enterobacteriaceae populations were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Nine (6%) of these, 4 domestic samples and 5 imported samples, were positive for Cronobacter spp. and the level was 0.36-0.91 MPN/100 g. Palcich et al [28] analyzed 186 PIF samples from Brazil with a target age of infants of 0-6 months. Cronobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine (6%) of these, 4 domestic samples and 5 imported samples, were positive for Cronobacter spp. and the level was 0.36-0.91 MPN/100 g. Palcich et al [28] analyzed 186 PIF samples from Brazil with a target age of infants of 0-6 months. Cronobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…An informed assessment of neonatal exposure warrants further investigation for the prevalence of Cronobacter spp., especially CC4, in PIF and other sources. Previous studies of hospital practices following Cronobacter outbreaks have shown that equipment used for formula reconstitution and feeding practices can be significant risk factors [25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…Cuantifi cación por número más probable (NMP): Se utilizó la técnica descrita por Palcich y cols (23). Los límites se establecieron de 0,009 a 316 NMP/g de LP con un 95% de confi anza.…”
Section: Materiales Y Métodosunclassified
“…When using powdered formula it is essential that it be prepared hygienically with good hand washing, clean water (ideally boiled) and clean utensils. There is a very small risk of bacterial contamination in powdered milk formula with Enterobacter sakasakii, a rare opportunistic pathogen associated with meningitis, necrotizing enterocolitis and sepsis (Gurtler et al, 2005;Palcich et al, 2009). As pointed out in a study in Tanzania, this is of particular concern in the preterm, but can occur at any age (Gurtler, et al, 2005;Mshana et al, 2011).…”
Section: Alternate Feedings In Premature and Sick Infantsmentioning
confidence: 99%